2008
DOI: 10.1016/j.brainresrev.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine spillover after quantal release: Rethinking dopamine transmission in the nigrostriatal pathway

Abstract: The predominance of dopamine (DA) receptors at extrasynaptic versus synaptic sites implies that dopamine signaling is by diffusion-based volume transmission. In this review, we compare characteristics that regulate extracellular DA behavior in substantia nigra pars compacta (SNc) and striatum, including regional differences in structure (a 40% greater extracellular volume fraction in SNc vs. striatum) and in dynamic DA uptake (a 200-fold greater DA uptake rate in striatum vs. SNc). Furthermore, we test the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
317
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(331 citation statements)
references
References 60 publications
11
317
1
2
Order By: Relevance
“…VT mediated by monoamines seems to depend on extrasynaptic release and transmitter spread to extrasynaptic receptors [11,14,15,18,33] since inter alia a large proportion of monoamine terminals lack postjunctional complexes [34,35]. Rice & Cragg [36] have modelled DA extrasynaptic transmission from terminals based on DA spillover after quantal release, considering a large number of experimental data from their own and other groups. In the updated DA synapse, if present since many DA terminals are asynaptic, the DA release is unconstrained by the extrasynapic DA transporter (DAT), the diffusion process being too fast for the DAT.…”
Section: Comparison Between Soluble and Extracellular Vesicle-mediatementioning
confidence: 99%
“…VT mediated by monoamines seems to depend on extrasynaptic release and transmitter spread to extrasynaptic receptors [11,14,15,18,33] since inter alia a large proportion of monoamine terminals lack postjunctional complexes [34,35]. Rice & Cragg [36] have modelled DA extrasynaptic transmission from terminals based on DA spillover after quantal release, considering a large number of experimental data from their own and other groups. In the updated DA synapse, if present since many DA terminals are asynaptic, the DA release is unconstrained by the extrasynapic DA transporter (DAT), the diffusion process being too fast for the DAT.…”
Section: Comparison Between Soluble and Extracellular Vesicle-mediatementioning
confidence: 99%
“…Moreover, DA receptors and the DAT on DA cell bodies and dendrites are largely extrasynaptic [110,[114][115][116], as are D1 receptors on non-dopaminergic terminals in these regions [115,117]. Thus, somatodendritically released DA relies on volume transmission [53,118,119], with an efficacy regulated by the diffusion and uptake characteristics of the local extracellular microenvironment, and negligible contributions from enzymatic degradation [53,102]. Consistent with the higher density of DA somata and dendrites in the SNc and VTA than in the SNr (figure 1), experimentally determined uptake rates for DA in guinea pig midbrain slices are higher in SNc and VTA than in SNr [102].…”
Section: What Is the Role Of Volume Transmissionmentioning
confidence: 99%
“…Data from these experimental studies were then used to model the influence of a 20-vesicle point source, which produced sufficiently high [DA] o for DA receptor activation (assuming 10 nM sensitivity) up to 20 mm away, with a DA half-life at this distance of several hundred milliseconds [102]. This model also showed that diffusion rather than uptake was the most important determinant of DA time course in midbrain [53,102]. In contrast to these findings based on DA diffusion and uptake assessed using voltammetric detection, a different picture emerges from evaluation of D2-IPSCs, which appear to be largely diffusion independent [23,24,69].…”
Section: What Is the Role Of Volume Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various subtypes of extrasynaptic dopamine receptors [123][124][125] are located in projection neurons and interneurons as well as on the afferent nerve terminal networks.…”
Section: Extrasynaptic Signalling/volume Signallingmentioning
confidence: 99%